The propagation of Standard Language Ideology: exploring how a Grade One teacher in an urban, linguistically diverse, English-medium primary school conceptualises language - Rowley, Emma-Kate (School of Education, 2018)
In the context of unequal access to quality education in South Africa in a first language, and policy that relies upon outdated, inaccurate conceptions of language, this study looks at how a Grade One educator at an urban English-medium school (attended by a linguistically diverse cohort of mostly non-English home language speakers) in Cape Town thinks about and talks about language in her teaching practices. The central question it attempts to answer is: how does Ms L, a Grade One educator at South Star Primary School, conceptualise language in her teaching practices? In other words, what is language for Ms L? With an eye to answering this question, I examine the language practices of Ms L alongside the assumptions implicit in her interactions with learners about (what counts as legitimate) language use and language speakers. I draw on current sociolinguistic theory which posits that language is a situated social practice, and contrast this with the conception of language as an identifiable bounded entity that is ubiquitous in policy and curriculum statements. Using concepts from sociolinguistics and applied linguistics, I analysed transcriptions from two weeks of lesson recordings in Ms L's classroom. Ms L's teaching practices pointed to a conception of language as a system of parts, as a measurable skill, and languages as separable objects. Analysis of her language practices showed the use of mainly one named language, English, except during Afrikaans lessons where she attempted to use only Afrikaans, occasionally drawing on English linguistic resources for specific purposes. Learners were strongly discouraged from using more than one language at a time, and use of different languages were strictly demarcated according to the lesson being taught. Aside from this evidence pointing to a conception similar to that evident in policy - of language as an autonomous entity, and languages as distinct and distinguishable objects - many of the ways in which Ms L spoke about language also pointed to a standard language ideology. This is incompatible with multilingualism and is a symbolic devaluing of non-standard varieties and speakers.